2007
DOI: 10.1371/journal.pone.0001211
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Cell and Tissue Patterning in a Strained Fibrin Gel System

Abstract: Techniques developed for the in vitro reproduction of three-dimensional (3D) biomimetic tissue will be valuable for investigating changes in cell function in tissues and for fabricating cell/matrix composites for applications in tissue engineering techniques. In this study, we show that the simple application of a continuous strain to a fibrin gel facilitates the development of fibril alignment and bundle-like structures in the fibrin gel in the direction of the applied strain. Myoblasts cultured in this gel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
79
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 27 publications
6
79
0
2
Order By: Relevance
“…Therefore, frequently cell lines are used such as C2C12, which are satellite cells of C3H mice (Dennis et al, 2001;Borschel et al, 2004;Levenberg et al, 2005;Riboldi et al, 2005;Huang et al, 2006a;Boontheekul et al, 2007;Matsumoto et al, 2007). Also, satellite cells harvested from the soleus muscle of rats are used for TE of muscle tissue (Dennis and Kosnik, 2000;Beier et al, 2004;Stern-Straeter et al, 2005;Das et al, 2006;Borschel et al, 2006;Larkin et al, 2006;Bach et al, 2006;Huang et al, 2006b;Boontheekul et al, 2007).…”
Section: Progenitor Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, frequently cell lines are used such as C2C12, which are satellite cells of C3H mice (Dennis et al, 2001;Borschel et al, 2004;Levenberg et al, 2005;Riboldi et al, 2005;Huang et al, 2006a;Boontheekul et al, 2007;Matsumoto et al, 2007). Also, satellite cells harvested from the soleus muscle of rats are used for TE of muscle tissue (Dennis and Kosnik, 2000;Beier et al, 2004;Stern-Straeter et al, 2005;Das et al, 2006;Borschel et al, 2006;Larkin et al, 2006;Bach et al, 2006;Huang et al, 2006b;Boontheekul et al, 2007).…”
Section: Progenitor Cellsmentioning
confidence: 99%
“…Nanoscale features are more efficient in promoting the assembly of longer myotubes than microscale features (Huang et al, 2006a). Parallel alignment can also be induced by applying mechanical or magnetic strain: muscle fibres reorganize along the line of force (Sekine et al, 2006;Matsumoto et al, 2007) and through static magnetic fields (Coletti et al, 2007).…”
Section: Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…53 However, Matsumoto et al reported that after applying a continuous mechanical force, clots displayed bundle-like structures with fibrils that were oriented parallel to the strain direction. 77 In a later work by the same group, bone marrow-derived stromal cells (BMSCs) were cultured in a strained fibrin gel and exhibited a specific orientation which was identical to the strain direction, suggesting that structural changes in the gel provided contact guidance cues to promote cell alignment. Moreover, the direction of the cell proliferation as well as mineral deposition in the strained gel was restricted to the same direction.…”
mentioning
confidence: 99%
“…Specifically, cyclic mechanical stretching of cell-seeded scaffolds has been shown to improve myoblast alignment, myofiber diameter, and skeletal muscle construct hypertrophy (22,23). Importantly, mechanically loaded tissueengineered skeletal muscle constructs often more closely mimic the tissue elasticity, structural organization, and force generation capabilities of native skeletal muscle (24)(25)(26). In addition, there is some clinical evidence that massage therapy or the physical manipulation of injured skeletal muscle and connective tissue may reduce pain and promote recovery by increasing blood flow (27)(28)(29).…”
mentioning
confidence: 99%